2021
DOI: 10.1182/blood.2020007905
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T-cell reconstitution predicts survival outcomes after acute graft-versus-host-disease: a dual-center validation

Abstract: Acute Graft-versus-Host-Disease (aGvHD) is a major cause of morbidity and mortality after allogeneic hematopoietic cell transplantation (HCT). We previously showed that early CD4+ T-cell reconstitution (CD4+IR) predicts survival after HCT. Here, we studied the relation between CD4+ IR and survival in patients who developed aGvHD. Pediatric patients receiving their first allogeneic HCT at the UMC Utrecht / Princess Máxima Center (UMC/PMC) or Memorial Sloan Kettering Cancer Center (MSK), were included. Primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
0
26
1
Order By: Relevance
“…The abundance of naïve T cells in the graft may influence the outcome of patients after allogeneic HCT as long as thymic function has not been restored. Although total numbers of CD4 + T cells have been shown to directly correlate with survival post GvHD ( 10 , 11 ), levels of naïve T cells have been identified as the most potent drivers of alloreactivity ( 12 ). In agreement, high levels of CD4 + naïve T cells (but not of CD8 + T cells) in allografts have been observed to correlate with an increased incidence of acute GvHD (aGvHD) post transplantation ( 13 ).…”
Section: Distinct Importance Of Naïve and Memory T Cells And Significance Of T-cell Receptor Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…The abundance of naïve T cells in the graft may influence the outcome of patients after allogeneic HCT as long as thymic function has not been restored. Although total numbers of CD4 + T cells have been shown to directly correlate with survival post GvHD ( 10 , 11 ), levels of naïve T cells have been identified as the most potent drivers of alloreactivity ( 12 ). In agreement, high levels of CD4 + naïve T cells (but not of CD8 + T cells) in allografts have been observed to correlate with an increased incidence of acute GvHD (aGvHD) post transplantation ( 13 ).…”
Section: Distinct Importance Of Naïve and Memory T Cells And Significance Of T-cell Receptor Diversitymentioning
confidence: 99%
“…Moreover, as IR is age dependent, this and other reviews are hampered by the lack of data from a primarily paediatric setting ( 7 ). Table 1 provides published data on immune cell subsets in adaptive IR and their relation to aGvHD after HCT in paediatric and adult patients ( 10 , 11 , 17 – 19 , 49 , 98 , 100 110 ).…”
Section: Immune Reconstitution and Acute Gvhd: The “Chicken And Egg” Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have recently shown that adequate CD4+ T-cell IR (CD4 + IR) is crucial for favorable survival outcomes [ 1 , 2 , 6 8 ]. Patients with adequate CD4 + IR (>50 × 10 6 CD4+ T-cells/L blood, within 100 days after HCT) had a lower risk of viral reactivation [ 1 ], virus-related morbidity and mortality [ 1 ], aGvHD-related mortality [ 27 ], and relapse-related mortality [ 6 , 8 ]. In addition, IR of other immune cell subsets, such as natural killer (NK)-cells [ 28 30 ], CD8+ T-cells [ 31 33 ], and B-cells [ 34 39 ], were also related to HCT outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This association is based on the contribution of the helper T cell immunity in ensuring pathogen defence against CMV and other common viruses as well as its major role in the alloreactive eradication of residual malignant cells after HCT [ 13 ]. Despite the successful validation of these T helper cell cut-off levels in paediatric patients receiving T cell depletion with anti-thymocyte globulin (ATG) [ 14 ], in patients with graft-versus-host disease (GVHD) [ 15 ], and in HCT with different graft sources [ 16 ], their application in the context of CMV exposed patients is limited by the median onset of the first CMV reactivation episodes after HCT, which is as early as day+33 without prophylaxis [ 5 ]. We hypothesized that an unsupervised machine learning approach, namely a k -means data clustering, of CD4 + helper T cell counts at day+30 after HCT, combined with the R serostatus might identify early predictors of CMV-dependent clinical outcomes, and thus might improve the CMV-based risk assessment post-transplantation.…”
Section: Introductionmentioning
confidence: 99%